Effects of different aerobic exercise frequencies on streptozotocin-nicotinamide-induced type 2 diabetic rats: Continuous versus short bouts and weekend warrior exercises - KURTEL, HIZIR (WILEY, 2018)
Background: Exercise training is known to have multiple beneficial effects on type 2 diabetes mellitus (T2DM). The aim of this study was to explore the effects of aerobic exercise frequency on diabetic parameters, the histopathological structure of skeletal muscle, diabetic myopathy, and mitochondrial enzyme activity in an experimental model of T2DM. Methods: Sprague-Dawley rats (n = 35) were rendered diabetic by injection of nicotinamide (110 mg/kg) and streptozotocin (65 mg/kg). Rats with blood glucose concentrations between 7 and 17 mmol/L were used. Diabetic rats were randomly allocated to one of the following groups: (i) control sedentary; (ii) diabetic sedentary; (iii) diabetic with continuous exercise (30 min/day, 5 days/week); (iv) diabetic with short bouts of exercise (3 x 10 min/day, 5 days/week); and (v) diabetic rats as weekend warriors (35 + 40 min/day, 2 days/week). After 6 weeks swimming exercise (total duration 150 min/week), biochemical tests were performed to measure insulin, glucose, cytokines, serum and muscle myeloperoxidase (MPO), and malondialdehyde (MDA) levels. Histologic analysis (histomorphometric and mitochondrial enzyme analysis) was also performed. Results: Compared with diabetic sedentary rats, significant improvements were observed in all exercise groups in terms of glucose levels, weight loss, tissue MPO and MDA levels, muscular connective tissue, muscle atrophy, mitochondrial enzyme, and all histomorphometric analyses. Conclusions: The results of the study emphasize the effects of training on inflammation, increased oxidative stress, myopathy, and mitochondrial damage in a rat model of T2DM, and demonstrate that there is no major difference between exercise modalities provided that the total duration of exercise remains the same.
Keywords: diabetic myopathy; physical activity; short bouts of exercise; type 2 diabetes mellitus; weekend warrior; SKELETAL-MUSCLE; PHYSICAL-ACTIVITY; AMERICAN-COLLEGE; SPORTS-MEDICINE; MELLITUS; HEALTH; NIDDM; ASSOCIATION; DURATION; INSULIN